(untitled) (Annals of Medical Research, 2021)
Caustic esophageal burns may cause many somatic, mental, and social problems. One of the major sequels is the loss of one’s own esophagus. Taking a start from the concept that "for such accidents, the best is to prevent children from contacting the corrosive substances", we made an epidemiological survey. In the first section, we analyzed the parents’ attitudes for caustic ingestion, questioning whether they have some precautions at home or not, their level of awareness on caustics. In the second section, we detailed the first- aid at home. Thirdly, we questioned parents’ awareness about the law. In the first part, we found that the parents, in general, were aware of drugs trying to prevent their children by keeping the drugs etc. In the second part, we found that almost 70% of parents’ choices for the final approach in first aid at home was to visit a doctor’s office or a health facility. We did not observe such satisfactory results when we questioned the law aspect of such accidents. Almost 50% of the parents agreed on their responsibility of guilt but most of them did not know the rule of Turkish law about such ingestion or accidents. This study stresses out that, when individually evaluated, the parents’ attitudes for caustics etc. are not generally in the wrong direction, but still there is much to do to inform the parents especially the ones who have given the wrong answers both on the medical aspects and the rules of the law. It is worth to spend a multicenter and multinational effort on the preventive aspect of this problem to document the differences of the communities and what is more important for every community in the study, what are the common denominators and what can be done for prevention and if possible, eradication of such a problem by people involved in treating such patients.